Evaluation of the relationship between corneal diameter and lens diameter in children - Wong, CL; Mae-Lynn Catherine Bastion,; Ropilah AR,; Jamalia R, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Primary intraocular lens (IOL) implantation has gained acceptance for management of infantile cataracts because of the advantage of reduced amblyopia risk. The aim of the study was to investigate the association between corneal diameter as measured from the white-to-white distance and natural lens diameter in children. This association may aid intraocular lens selection following cataract removal in infants and young children. A cross-sectional study was performed on forty eyes from 40 children less than 4 years, who needed to be examined, were planned for a procedure or operation under general anaesthesia. Subjects were recruited from Eye Clinic,Kuala Lumpur General Hospital from January 2010 to September 2011. Corneal diameter was measured with Holladay-Godwin corneal gauge while lens diameter was measured with ultrasound biomicroscope (UBM) during surgery. For the results, mean age of subjects was 24.7 + 12.1 months. Mean corneal diameter was 11.62 + 0.50 mm horizontally and 11.20 + 0.58 mm vertically. Mean horizontal lens diameter was 7.94 + 0.47 mm. A medium positive correlation was found between mean horizontal corneal diameter and lens diameter (r=0.479, p=0.002). Lens diameter had a strong correlation with patient’s age (r=0.718, p<0.001). Lens diameter can be calculated by using this model of equation: [Lens diameter (mm) = 7.010 + 0.021 Corneal Diameter (mm) + 0.028 Age (months)] (r2 =0.52). In conclusion, there was a moderate positive correlation between corneal and lens diameter. UBM can be used to measure lens capsular bag size directly preoperatively.